RANCANG BANGUN ALAT MONITORING POLUSI UDARA BERBASI ARDUINO - LAHAL, ARKIPUS; Suharyanto, Cosmas Eko (LPPM Universitas Putera Batam, 2021)
Air pollution is a problem that is still unresolved. Air pollution can occur due to incomplete combustion of vehicle engines or industrial processes that produce gases that are not good for health. Gaseous compounds contained in polluted air can have a negative impact on health if the levels exceed normal limits. Therefore, this study aims to increase awareness of the importance of healthy air quality, so that people will be more concerned about health and can minimize the risk of breathing harmful air. In this study, an air pollution monitoring tool is offered which not only functions as a monitor but also determines the level of air pollution content. The monitoring system in this study is equipped with an MQ135 sensor which functions as an air pollution detector. The results of air quality monitoring in this study will show 2 conditions of ambient air quality, namely: good and bad. With this information, people can know whether the place is safe or dangerous for their health. The Department of Environment tests gas emissions from two-wheeled to four-wheeled vehicles because many vehicles have emitted gas emissions that can interfere with the air we breathe, besides the broad impact that can interfere with public health, such as asthma, cancer, lung disease. lungs, and so on. Because of this, researchers want to provide awareness to the public about the importance of air health for both pedestrians and those who drive to breathe healthier air.